Beliefs and attitudes of Syrian refugee mothers in Lebanon regarding children vaccination: a cross-sectional study - Issam Shaarani; Sleiman Khadem; Marwa Obeid; Behnaz Saadieh; Aya Serhal; Karim Zakkour; Sara Mohammad; Hussein Berjaoui; Nour Izmirli (BMC Public Health)
Abstract Background Vaccines have contributed to the disappearance of various diseases, and almost eradicated others across the world. Studies have shown that in Lebanon a profoundly small percentage of Syrian refugee children were fully immunized by routine vaccination services. Exploring the knowledge, attitudes, and practices of parents towards vaccination is of crucial importance, given the role of parents in children’s immunization. This study aims to investigate the knowledge, attitudes, and practices of the Syrian refugee mothers in Lebanon towards the immunization of their children. Methods This is a cross-sectional study conducted using questionnaires targeting Syrian refugee mothers whose children were born on Lebanese grounds, are below the age of five, and are following the Lebanese vaccination schedule. Results Majority of refugee mothers considered vaccination to be safe (89.9%) and stated that vaccination should be initiated at birth (87.2%). Almost all of the interviewed mothers plan to vaccinate their children according to the National Lebanese Vaccination Schedule. Concerning the children’s immunization status, 51.4% of Syrian refugee children were fully immunized and 48.6% had aberrant vaccination. Conclusion Although refugee mothers had some knowledge gaps regarding vaccines, the main issue lies within the accessibility. A collaborative coordinated approach involving governmental and non-governmental agencies seems to be an effective approach to improve rates of immunization.